Quantitative assessment of nutrition and nutritional status of patients with celiac disease aged 13-18 - Justyna Kikut; Nina Konecka; Małgorzata Szczuko (National Institute of Public Health - National Institute of Hygiene, 2019)
Background. Celiac disease is an autoimmune disease that affects about 1% of the European population and 0.3-1.3% of the world's population. The only method of treatment is introduction of a gluten-free diet. Objective. The aim of the study was to assess the nutrition of adolescents with celiac disease and to assess their nutritional status. Materials and methods. The study group comprised 24 patients with diagnosed celiac disease. The diagnosis was based on biopsy, serological tests and, in some cases, genetic tests. Anthropometric measurements included height, which was respectively 161.9 ±12.43 cm in boys and 163.6 ±9.03 cm in girls, and body weight oscillating between 56.55 ±16.24 kg for boys and 52.62 ±10.92 kg for girls. To assess the way of nutrition used an individually prepared questionnaire including an interview from the last 24 h. The menus were analyzed using the Dieta 5d program. The statistical analysis of the data was made using Statistica 12 program. Results. Gluten-free diet contributes to the occurrence of caloric deficiencies up to 36%. It was found inadequate intake of dietary fiber, for girls 15.45 ±9.84 g and 14.41 ±4.73 g for boys. It has been observed too low intake of ingredients such as calcium (565.65 ±347.41 mg), magnesium (223.41 ±73.84 mg), vitamin D (1.34 ±1.28 μg) and E (5.05 ±2.32 mg) as well as potassium (2848.67 ±1132.07 mg), iron (7.62 ±2.05 mg), zinc (7.11 ±2.41 mg) and thiamine (0.87 ±0.38 mg). The ingredients such as riboflavin, niacin, pyridoxine, cobalamin, and vitamins C and A were consumed in the right amount. Conclusions. Incorrectly used gluten-free diet may contribute to the recurrence of the disease. Chronic inadequate intake of fiber can lead to constipation. A deficiency of many nutrients can result in impaired development of the young organism such as anemia, growth retardation or osteoporosis.